Sistem Pengetahuan Kaum Perempuan Suku Enggros Mengenai Hutan Mangrove di Kota Jayapura - Marlina Flassy; Simon Abdi K. Frank; Usman Idris; Soraya Maydeline Marani (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
This research aims to analyze the knowledge system of women from the Enggros tribe regarding mangrove forests and their utilization patterns. Descriptive qualitative research employs an ethnographic approach. We conducted the research in both Tobati village and Enggros village. Data collection techniques used include in-depth interviews, observations, and literature reviews. We determined the informants through a snowball method, selecting the village head as the primary informant. Interview guidelines, picture and sound recording devices, and field notebooks were among the instruments used. Data analysis techniques included data reduction, presentation, verification, and conclusion drawing. The results demonstrated that the women's knowledge system of the Kampung Enggros Mangrove Forest encompasses their understanding of the mangrove forests. This includes their understanding of when to search for shellfish before entering the mangrove forest area (ton), how to search for shellfish about the prohibition on men entering the mangrove forest area (ton), and their understanding of the results obtained from the mangrove forest area (ton). Additionally, the women of Enggros Village uphold deeply ingrained traditional values in their customs, ensuring their continued adherence to the customs and traditions that endure to this day. Next, they follow the tradition of using mangrove forests (ton) as a means of subsistence and a venue for storytelling.